The acute effect of resistance exercise on serum growth hormone and blood glucose in healthy non-obese adolescent subject - Madavi, Hemant; Srivastava, Chitra; Kanawjia, Preeti; Saxena, Jalaj (International Journal of Research in Medical Sciences, 2021)
Background: The growth hormone (GH) response to resistance training is altered by many factors including sex steroid concentrations, fitness, intensity of exercise, age, gender, duration of exercise and glycemic state but the exact understanding of the interplay of different exercises to GH levels and its induced physiological adaptations is still obscure. This study aimed to see how resistance exercise affects GH levels and its correlation to plasma glucose levels in healthy non-obese adolescent subjects. Methods: 48 healthy non-obese adolescent subjects, 24 males and 24 females were included in the study. High volume exercise training regimen was used which involved major muscle group of arms, legs and trunk. Pre and post exercise levels of serum GH and random blood sugar were estimated in male and female groups. Results: The mean body mass index (BMI) of male and female groups was 23.22±3.12 kg/m2 and 20.40±4.49 kg/m2, respectively. The post-exercise serum GH levels in male and females increased significantly by 0.54±1.041 ng/ml (p<0.05) and 0.85±1.023 ng/ml (p<0.001) respectively. The random blood sugar levels in males after exercise significantly increased (p<0.05) by 7.16±12.61 mg/dl and in females by 6.20±12.09 mg/dl (p<0.05). There was significant correlation (p<0.05) between increase in serum GH levels and increase in random blood sugar levels in both male and female group. Conclusions: Exercise induced increase in GH and its interplay with serum glucose can be better gained access into via metanalytical/elaborate studies of the major hormones and fuels involved.